Increased Release of Proinflammatory Proteins in Primary Human Adipocytes and Activation of the Inflammatory NFĸB, p38, and ERK Pathways upon Omentin Treatment - Niersmann, Corinna (Obes Facts, 2020)
OBJECTIVES: To investigate the impact of omentin on the release of inflammation-related biomarkers and inflammatory pathways in primary human adipocytes. METHODS: Adipocytes were treated with or without omentin (500 and 2,000 ng/mL), and the supernatants were analyzed for inflammation-related biomarkers using proximity extension assay technology. Potential upstream regulators of the omentin-stimulated proteins were identified using Ingenuity Pathway Analysis. Protein levels of components of inflammatory pathways were measured using Western blotting. RESULTS: 2,000 ng/mL omentin induced the release of 30 biomarkers 97.1 ± 31.1-fold in the supernatants (all p < 0.05). Most biomarkers were proinflammatory chemokines and cytokines. We identified the transcription factor nuclear factor “kappa-light-chain-enhancer” of activated B cells (NFĸB) and the kinases p38 and extracellular signal-regulated kinase (ERK)1/2 as potential upstream regulators in silico. On the cellular level, treatment with 2,000 ng/mL omentin for 24 h enhanced the phosphorylation levels of NFĸB 2.1 ± 0.3-fold (p < 0.05), of p38 2.6 ± 0.4-fold (p < 0.05), and of ERK1/2 1.8 ± 0.2-fold (p < 0.05). CONCLUSIONS: These data argue that omentin exerts proinflammatory effects through the activation of the inflammatory NFĸB, p38, and ERK1/2 pathways in cultured primary adipocytes.